2007
DOI: 10.1111/j.1399-3062.2006.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide failure to control recurrent cytomegalovirus infection in the setting of renal failure after allogeneic stem cell transplantation

Abstract: Cytomegalovirus (CMV) reactivation is common in the allogeneic stem cell transplant setting but the incidence of CMV organ disease and mortality has been dramatically reduced by prophylactic or preemptive antiviral therapy. We report the case of a CMV-seropositive 46-year-old man with non-Hodgkin's lymphoma who underwent an unrelated allogeneic stem cell transplant from a CMV-seronegative HLA-matched unrelated donor. CMV encephalitis and colitis developed that was refractory to single-agent therapy. The CMV is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…There are also reports of efficacy studies in animal models with banzi virus, influenza B virus, and vaccinia virus (36) that showed either a lack of or very limited efficacy. Clinical trials in humans were also reported for HIV, CMV, and BK virus (38,(40)(41)(42)(43), with no conclusive results. It is reported that mean levels of circulating uridine in man are approximately 6 μM (44), spanning a range between 2.6 μM (45) and 21 μM (46).…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports of efficacy studies in animal models with banzi virus, influenza B virus, and vaccinia virus (36) that showed either a lack of or very limited efficacy. Clinical trials in humans were also reported for HIV, CMV, and BK virus (38,(40)(41)(42)(43), with no conclusive results. It is reported that mean levels of circulating uridine in man are approximately 6 μM (44), spanning a range between 2.6 μM (45) and 21 μM (46).…”
Section: Discussionmentioning
confidence: 99%
“…The antimalarial artesunate (127) has anti-CMV effects that may be clinically helpful, especially with resistant disease (128). Leflunomide (am immunosuppressive agent approved for rheumatoid arthritis) has antiviral activity and has been reported to clear CMV viremia in transplant recipients with resistant CMV (129-132), but failure has been reported (133).…”
Section: Kottonmentioning
confidence: 99%
“…This review yielded nine cases of CMV CNS disease in SCT recipients, which meet the criteria for CMV disease of the CNS. [4][5][6][7][8][9][10][11][12] Data from these nine cases along with the two UCLA cases (a total of 11 patients) are summarized in Table 1. Except for one pediatric patient, all patients were adults (median age, 46 years).…”
Section: Review Of Reported Casesmentioning
confidence: 99%